“You can definitely tell she's truly committed”: student-athletes’ discursive construction of athletic commitment during transitions in secondary school - Øydna, Marie Loka; Saarinen, Milla; Nielsen, Jens Christian; Bjørndal, Christian Thue (Frontiers in Sports and Active Living, 2025)
In this paper, we present how two female and one male student-athlete discursively construct and make sense of the “committed athlete”, highlighting key shifts across transitions between school levels and high-performance sport environments. Applying a Foucauldian perspective on power/ knowledge and vignettes from follow-up interviews, this paper highlights the relational nature of commitment, showing how it is shaped by broader discourses and institutional structures. Our analysis shows that a discourse of athletic performance investment dominates these transitions, yet the student-athletes also negotiate less instrumentalised constructions of the committed athlete as someone with internal love for the activity itself. However, as they move into upper secondary school programmes and more professionalised club environments, they are faced with fewer possibilities to enact alternative meanings of commitment. We argue that student-athletes positioned as talented are better able to benefit from holistic development initiatives within the talent development system, while those outside these hierarchies face limited possibilities to negotiate alternative forms of commitment. This analysis invites a critical rethinking of how dual career pathways might expand the discursive possibilities for what it means to be a committed athlete.